The Effects of Dexmedetomidine on Secondary Acute Lung and Kidney Injuries in the Rat Model of Intra-Abdominal Sepsis - Uğur Koca; Çimen Gülben Olguner; Bekir Uğur Ergür; Emel Altekin; Aydın Taşdöğen; Seden Duru; Pelin Girgin; Kerim Gündüz; Serap Cilaker Mıcılı; Seda Güzeldağ; Muhammed Akkuş (The Scientific World Journal)
In the present study, the effects of dexmedetomidine on secondary lung and kidney injuries were studied in the rat model of intra-abdominal sepsis by immunohistological and biochemical examinations. We measured serum creatinine, kidney tissue malondialdehide and plasma neutrophil gelatinase-associated lipocalin levels. In order to evaluate tissue injury we determined kidney tissue mononuclear cell infiltration score, alveolar macrophage count, histological kidney and lung injury scores and kidney and lung tissue immunoreactivity scores. We demonstrated that dexmedetomidine attenuates sepsis-induced lung and kidney injuries and apoptosis in the rat model of sepsis. There is still need for comparative studies in order to determine the effects of dexmedetomidine on organ functions in early human sepsis.